Review of Questions Concerning Clinical Drug Interactions in ADHD Treatment From Physicians in Norway - Schjøtt, Jan; Heitmann, Kristine; Bakkebø, Tina; Jahnsen, Jan Anker (Frontiers in Pharmacology, 2020)
Pharmacological treatment of attention deficit hyperactivity disorder (ADHD) is challenging due to a wide age span among patients, risk of reduced adherence, and comorbidities like psychiatric disorders and drug addiction. Drugs used for ADHD are associated with risk of interactions and adverse drug reactions due to their potent pharmacological effect. In this brief report we aimed to describe real-world problem areas concerning interactions in pharmacotherapy of ADHD. We reviewed questions to a Norwegian drug information center from physicians concerning drug-drug interactions involving ADHD drugs in the last 10-year period. Questions were retrieved by a combination of indexed and Boolean database searches, in addition to manual inspection. ADHD drugs and interacting drugs were defined according to the Anatomical Therapeutic Chemical (ATC) classification system. Interactions were classified by use of Stockley's Interactions Checker (SIC). Answers were examined with regard to whether the advice from the drug information center was more restrictive, similar or more liberal than SIC when assessing drug combinations. We retrieved 61 questions that included assessment of 96 drug combinations, and found 33 potential interactions according to SIC. Methylphenidate was involved in more than 50% of the interactions, and interacting drugs were in nearly 70% of the cases from ATC-group N (Nervous system) with antidepressants most frequently involved. Seventy percent of the interactions were pharmacodynamic, and interactions were frequently described as potentially severe although they were based on theoretical evidence. All the 33 interactions could be handled with monitoring or adjusting dose or with informative measures, and none was contraindicated according to SIC. More than 90% of the questions came from physicians in hospitals or outpatient specialist practice, and questions mainly concerned adults. In 75% of the drug combinations that involved ADHD drugs, we found similar advice from SIC and the drug information center. Our results suggest that future drug information efforts in ADHD treatment to clinicians, including specialists in the field, should focus on psychotropic interactions.